FRGS/1/2018/SKK09/UIAM/02/6/ Pattern analyzer on concomitant use of opioid and benzodiazepine in patients with chronic non-cancer pain: the rising of opioid overdose death - Zin, Che Suraya (2022)
The practice of combining opioids and benzodiazepines has been recognized as both ubiquitous and substantial.[6] The extent to which the utilization of concurrent use of opioids and benzodiazepines and its clinical outcomes in Malaysia is unclear, but their co-prescribing presents a serious safety concern and is not well characterized. Given these uncertainties, this study was prompted to address the above-mentioned issues.